Efficacy and safety of luspatercept versus epoetin alfa in erythropoiesis-stimulating agent-naive, transfusion-dependent, lower-risk myelodysplastic syndromes (COMMANDS): interim analysis of a phase 3, open-label, randomised controlled trial - Platzbecker, Uwe; Della Porta, Matteo Giovanni; Santini, Valeria; Zeidan, Amer M; Komrokji, Rami S; Shortt, Jake; Valcarcel, David; Jonasova, Anna; Dimicoli-Salazar, Sophie; Tiong, Ing Soo; Lin, Chien-Chin; Li, Jiahui; et al. (Lancet (London, England), 2023)
BACKGROUND: Erythropoiesis-stimulating agents (ESAs) are the standard-of-care treatment for anaemia in most patients with lower-risk myelodysplastic syndromes but responses are limited and transient. Luspatercept promotes late-stage erythroid maturation and has shown durable clinical efficacy in patients with lower-risk myelodysplastic syndromes. In this study, we report the results of a prespecified interim analysis of luspatercept versus epoetin alfa for the treatment of anaemia due to lower-risk myelodysplastic syndromes in the phase 3 COMMANDS trial. METHODS: The phase 3, open-label, randomised controlled COMMANDS trial is being conducted at 142 sites in 26 countries. Eligible patients were aged 18 years or older, had a diagnosis of myelodysplastic syndromes of very low risk, low risk, or intermediate risk (per the Revised International Prognostic Scoring System), were ESA-naive, and required red blood cell transfusions (2-6 packed red blood cell units per 8 weeks for ≥8 weeks immediately before randomisation). Integrated response technology was used to randomly assign patients (1:1, block size 4) to luspatercept or epoetin alfa, stratified by baseline red blood cell transfusion burden (<4 units per 8 weeks vs ≥4 units per 8 weeks), endogenous serum erythropoietin concentration (≤200 U/L vs >200 to <500 U/L), and ring sideroblast status (positive vs negative). Luspatercept was administered subcutaneously once every 3 weeks starting at 1·0 mg/kg body weight with possible titration up to 1·75 mg/kg. Epoetin alfa was administered subcutaneously once a week starting at 450 IU/kg body weight with possible titration up to 1050 IU/kg (maximum permitted total dose of 80 000 IU). The primary endpoint was red blood cell transfusion independence for at least 12 weeks with a concurrent mean haemoglobin increase of at least 1·5 g/dL (weeks 1-24), assessed in the intention-to-treat population. Safety was assessed in patients who received at least one dose of study treatment. The COMMANDS trial was registered with ClinicalTrials.gov, NCT03682536 (active, not recruiting). FINDINGS: Between Jan 2, 2019 and Aug 31, 2022, 356 patients were randomly assigned to receive luspatercept (178 patients) or epoetin alfa (178 patients), comprising 198 (56%) men and 158 (44%) women (median age 74 years [IQR 69-80]). The interim efficacy analysis was done for 301 patients (147 in the luspatercept group and 154 in the epoetin alfa group) who completed 24 weeks of treatment or discontinued earlier. 86 (59%) of 147 patients in the luspatercept group and 48 (31%) of 154 patients in the epoetin alfa group reached the primary endpoint (common risk difference on response rate 26·6; 95% CI 15·8-37·4; p<0·0001). Median treatment exposure was longer for patients receiving luspatercept (42 weeks [IQR 20-73]) versus epoetin alfa (27 weeks [19-55]). The most frequently reported grade 3 or 4 treatment-emergent adverse events with luspatercept (≥3% patients) were hypertension, anaemia, dyspnoea, neutropenia, thrombocytopenia, pneumonia, COVID-19, myelodysplastic syndromes, and syncope; and with epoetin alfa were anaemia, pneumonia, neutropenia, hypertension, iron overload, COVID-19 pneumonia, and myelodysplastic syndromes. The most common suspected treatment-related adverse events in the luspatercept group (≥3% patients, with the most common event occurring in 5% patients) were fatigue, asthenia, nausea, dyspnoea, hypertension, and headache; and none (≥3% patients) in the epoetin alfa group. One death after diagnosis of acute myeloid leukaemia was considered to be related to luspatercept treatment (44 days on treatment). INTERPRETATION: In this interim analysis, luspatercept improved the rate at which red blood cell transfusion independence and increased haemoglobin were achieved compared with epoetin alfa in ESA-naive patients with lower-risk myelodysplastic syndromes. Long-term follow-up and additional data will be needed to confirm these results and further refine findings in other subgroups of patients with lower-risk myelodysplastic syndromes, including non-mutated SF3B1 or ring sideroblast-negative subgroups. FUNDING: Celgene and Acceleron Pharma.
Keywords: senioři; neutropenie; Neutropenia; Hypertension; lidé; Dyspnea; Myelodysplastic Syndromes; mužské pohlaví; COVID-19; Hemoglobins; Anemia; Epoetin Alfa; Body Weight; myelodysplastické syndromy; hematinika; ženské pohlaví; epoetin alfa; Humans; erytropoéza; Erythropoiesis; tělesná hmotnost; Hematinics; hypertenze; dyspnoe; hemoglobiny; Female; Aged; anemie; Male